2020
DOI: 10.1007/s10606-020-09382-0
|View full text |Cite
|
Sign up to set email alerts
|

How Does Collaborative Reflection Unfold in Online Communities? An Analysis of Two Data Sets

Abstract: People can learn a lot through (collaborative) reflection at work: In organizations, staff debate experiences and due to issues every day, thus reflecting together and learning from each other. While this is desirable, it is often hindered by differences in time and space. Online discussions in community-like systems may provide a means to overcome this issue and enable staff to share experiences and learn from them. In this paper, we study two different data sets from two software systems to support online co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…An encountered problem is the experience required by the teacher to moderate the reflection process and to identify reflection-worthy moments in the group work. Reflections follow paths even if these are not yet clearly identified [19]; thus, further research should be done to identify the domain-specific reflection paths of conceptual modeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An encountered problem is the experience required by the teacher to moderate the reflection process and to identify reflection-worthy moments in the group work. Reflections follow paths even if these are not yet clearly identified [19]; thus, further research should be done to identify the domain-specific reflection paths of conceptual modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Huge benefits from reflective learning are researched and identified in different areas including but not limited to: computer-supported collaborative work (CSCW) in co-located teams [14,15,16,17]; as well as in asynchronous online communities [18,19]; design thinking and designing of business models [20,21]; in computer-supported collaborative learning (CSCL) [22,23] and (teacher) education [24,25,26]. These various approaches and concepts are unified in their shared insights on the importance of reflective learning and the challenge to create effective facilitation for each domain's unique requirements for reflection support.…”
Section: Computer-supported Reflectionmentioning
confidence: 99%
“…Reflection processes, such as individual activities, are embedded in a social context. Although reflection is an individual activity, it can be performed together with others, concerning collective reflection ( Raelin, 2002 ; Schley and Van Woerkom, 2014 ; Foong et al, 2018 ; Prilla et al, 2020 ). Collective reflection can be considered a social learning activity that occurs together with others and thus influences the intrapersonal process of reflection.…”
Section: Development Of a Conceptual Modelmentioning
confidence: 99%
“…More importantly, it may help learners come up with solutions to problems that are not likely to be inspired by individual reflections (Fakazli and Kuru Gönen, 2017). Compared with other modes such as diaries or videos, collaborative reflection received fewer negative perceptions from students (Fakazli and Kuru Gönen, 2017;Prilla et al, 2020). However, some studies also reported problems with collaborative reflection such as distraction and awkwardness (Epler et al, 2013).…”
Section: Reflection and Reflection Modementioning
confidence: 99%